An Analysis of the Causes of Delays in the Return of Outpatient Medical Records at Jambesari Public Health Center, Bondowoso - Kiromah, Siska Ainul; Nuraini, Novita; Deharja, Atma; Sabran, Sabran (P3M Politeknik Negeri Jember, 2024)
Timely return of medical records is essential for evaluating the quality of services at Community Health Centers (Puskesmas). In the second quarter of 2022, Puskesmas Jambesari in Bondowoso experienced a significant delay in the return of outpatient medical records. Of the 1,822 expected files, 1,443 (approximately 80%) were returned late, resulting in frequent misfiling due to improper storage. The prolonged absence of these records was a major contributing factor to the issue. This study aims to analyze the underlying causes of delays in returning outpatient medical records at Puskesmas Jambesari by examining the seven elements of the 7M framework: manpower, money, materials, machines, methods, motivation, and media. Employing a qualitative research approach, data were collected through interviews, observations, documentation, and brainstorming sessions. The findings reveal several systemic issues: front desk staff lacked awareness of return deadlines; training for relevant personnel was insufficient; the use of tracers and phone communication was minimal; expedition books were not optimally utilized; no specific Standard Operating Procedure (SOP) existed for record return; motivational incentives were absent; the physical storage space for records was inadequate; and no budget proposal had been prepared to support improvements. Notably, the absence of a clear SOP further exacerbated the problem.